Assessment of Toxicological impact of light crude oil on clarias gariepus (Burechell, 1822) fingerlings (2005)
Oil spillage is of critical concern in Nigeria because of the problems of pollution and associated disturbances. It is therefore necessary to study the effects of oil pollution on fish using clarias gariepinus, a widely cultured fish species in the tropics. A short-term (96-hours), statics bioassay was carried out to determine the toxicity of crude oil (qua ibeo light) on C. gariepinus fingerlings. The biossay involved five treatment viz:0, 25, 50, 75, and 100µL/L. The water and fish samples were analyzed for total hydrocarbon content (THC) and heavy metals at the end of the experiment. There were significant differences (p<0.05) among the five treatments. The LC50 ( concentration at which 50 percent of the test population died) was 1.58µL/L. Lead, iron, cadmium and chromium were not detected in the water contaminated with the crude oil sample.